Management Pendidikan Berbasis Keunggulan Lokal - Muhammad Mahfud (ZAHRA: Research and Tought Elementary School of Islam Journal, 2020)
ABSTRACT Local Excellence (KL) is a process and realization of increasing the value of a regional potential so that it becomes a product /service or other work of high value, is unique and has a comparative advantage. The quality of the process and the realization of local excellence is greatly influenced by the available resources, which are better known as 7 M, namely Man, Money, Machine, Material, Method, Marketing and Management. The concept of developing local excellence is inspired by various potentials, namely the potential of natural resources (SDA), human resources (HR), geographical, cultural and historical. Natural resources (SDA) are the potential contained in the earth, water, and aerospace that can be utilized for various life purposes. Human resources (HR) are defined as humans with all the potential they have that can be utilized and developed to become social creatures that are adaptive and transformative and able to utilize the natural potential around them in a balanced and sustainable way. Geographic objects include, among others, formal objects and material objects. Culture is attitude, while the source of attitude is culture. Local excellence in historical concepts is historical potential in the form of relics of ancient objects and traditions that are still preserved today.